Nonalcoholic Fatty Liver Disease and Type 2 Diabetes Mellitus: A Bidirectional Relationship - Cristina M. Muzica; Catalin Sfarti; Anca Trifan; Sebastian Zenovia; Tudor Cuciureanu; Robert Nastasa; Laura Huiban; Camelia Cojocariu; Ana-Maria Singeap; Irina Girleanu; Stefan Chiriac; Carol Stanciu (Canadian Journal of Gastroenterology and Hepatology)
Worldwide, the leading cause of chronic liver disease is represented by nonalcoholic fatty liver disease (NAFLD) which has now become a global epidemic of the 21st century, affecting 1 in 4 adults, and which appears to be associated with the steadily increasing rates of metabolic syndrome and its components (obesity, type 2 diabetes mellitus (T2DM), and dyslipidemia). NAFLD has been reported to be associated with extrahepatic manifestations such as cardiovascular disease, T2DM, chronic kidney disease, extrahepatic malignancies (e.g., colorectal cancer), endocrine diseases (e.g., hypothyroidism, polycystic ovarian syndrome, psoriasis, and osteoporosis), obstructive sleep apnea, and iron overload. The prevalence of NAFLD is very high, affecting 25–30% of the world population and encloses two steps: (1) nonalcoholic fatty liver (NAFL), which includes steatosis only, and (2) nonalcoholic steatohepatitis (NASH) defined by the presence of steatosis and inflammation with hepatocyte ballooning, with or without fibrosis which can progress to liver fibrosis, hepatocellular carcinoma, and liver transplantation. Current data define a more complex relationship between NAFLD and T2DM than was previously believed, underlining a bidirectional and mutual association between the two entities. This review aims to summarize the current literature regarding the incidence of T2DM among patients with NAFLD and also the prevalence of NAFLD in T2DM patients, highlighting the recent key studies. Clinicians should screen, diagnose, and treat T2DM in patients with NAFLD in order to avoid short- and long-term complications.